Analisis Pengaruh Fitur User Interface Ramah Pengguna Terhadap Tingkat Loyalitas Pelanggan di Tokopedia - Septanto, Henri; Ari Hidayatullah; Harya Bima Dirgantara (KALBISCIENTIA Jurnal Sains dan Teknologi, 2024)
This research aims to analyze the influence of user-friendly user interface features on the level of customer loyalty in the Tokopedia application. In an increasingly advanced digital era, user experience is a crucial factor in maintaining and increasing customer loyalty. Tokopedia, as one of the largest market place platforms in Indonesia, continues to develop UI features that make navigation easier, increase interaction and enrich the shopping experience. This research uses a survey method involving 50 active Tokopedia users to collect data regarding their perceptions of the application's UI features. Data analysis was carried out using simple quantitative descriptive processing techniques to identify the relationship between user-friendly UI and customer loyalty. The research results show that there is a significant positive correlation between intuitive and easy-to-use UI features and the level of customer loyalty. Users who feel comfortable and satisfied with the application interface tend to make repeat transactions more often and recommend Tokopedia to others. These findings emphasize the importance of investing in user-friendly UI development as a strategy to increase customer satisfaction and loyalty in the competitive e-commerce market.Keywords: user interface, loyalty, application, market place